Much Ado about Nothing? School Curriculum Reforms and Students' Educational Trajectories - Maurizio Strazzeri; Chantal Oggenfuss; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2022)
We estimate the impact of a large curriculum reform in Switzerland that substantially increased the share of foreign language classes in compulsory school on students' subsequent educational choices in upper secondary school. Using administrative student register data and exploiting the staggered implementation of the curriculum reform, we find that exposure to more foreign language classes during compulsory school has only minor effects on educational choices of the overall student population. However, we find substantial effect heterogeneity: while the reform has no effect on the direct educational progression of either low-track female or high-track students, it impedes low-track male students' transition to upper secondary education. The effect of foreign language classes on the educational trajectory of low-track male students is particularly pronounced for students who do not speak at home the school's language of instruction. Finally, we find that female students who start vocational training immediately after compulsory school are more likely to select into training occupations that require higher foreign language skills instead of natural science skills.
Keywords: I21; I24; I28; 330; policy evaluation; Goodman-Bacon decomposition; education reform; foreign language skills; compulsory school; educational choices; occupational choices